2016
DOI: 10.1302/0301-620x.98b10.bjj-2016-0414.r1
|View full text |Cite
|
Sign up to set email alerts
|

Early outcomes of twin-peg mobile-bearing unicompartmental knee arthroplasty compared with primary total knee arthroplasty

Abstract: AimsSince redesign of the Oxford phase III mobile-bearing unicompartmental knee arthroplasty (UKA) femoral component to a twin-peg design, there has not been a direct comparison to total knee arthroplasty (TKA). Thus, we explored differences between the two cohorts.Patients and Methods A total of 168 patients (201 knees) underwent medial UKA with the Oxford Partial Knee Twin-Peg. These patients were compared with a randomly selected group of 177 patients (189 knees) with primary Vanguard TKA. Patient demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 45 publications
1
22
0
2
Order By: Relevance
“…A further 36 cohort studies were included in group 3. Of these studies including data comparisons between UKAs and TKAs,15 31 82 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 107 108 109 110 111 112 113 114 only five included data specifically in patients with anteromedial osteoarthritis 1585 99 103 111 Again, we saw some crossover in the data presented from the same unit in multiple papers, but the maximum number of implants was 26 418.…”
Section: Resultsmentioning
confidence: 99%
“…A further 36 cohort studies were included in group 3. Of these studies including data comparisons between UKAs and TKAs,15 31 82 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 107 108 109 110 111 112 113 114 only five included data specifically in patients with anteromedial osteoarthritis 1585 99 103 111 Again, we saw some crossover in the data presented from the same unit in multiple papers, but the maximum number of implants was 26 418.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have highlighted the advantages of UKR over total knee replacement (TKR) in patients with medial compartment OA, including reduced blood loss and risk of transfusion, 15,16 better restoration of physiological gait pattern, 17 shorter length of stay and a lower 30-day readmission rate, 18 better patientreported pain and function scores and forgotten joint scores. [19][20][21][22] Furthermore, a matched comparison of UKA and TKA based on NJR data including over 100,000 knee arthroplasties demonstrated that major medical complications, such as thromboembolism, infection, stroke and myocardial infarction occurred between a quarter and a half times less frequently in UKR than in TKR. Moreover, the mortality was significantly lower for UKR.…”
Section: Results Of Unicompartmental Versus Total Knee Replacementmentioning
confidence: 99%
“…45 Potential advantages of undergoing a PKR over a TKR for patients with medial compartment OA have been discussed in several registry and cohort studies. For example, studies have demonstrated reduced blood loss and risk of transfusion at the time of operation; 48,49 shorter length of stay and a lower 30-day re-admission rate; 50-52 more cost-effective, 53,54 better restoration of physiological gait pattern; 55 and better patient-reported pain and function scores and forgotten joint scores [56][57][58][59][60] for PKR compared with TKR. In addition, PKR has been reported to be more cost-effectiveness, 53,54 have lower incidence of medical complications, such as thromboembolism, infection, stroke and myocardial infarction, and lower mortality rates than TKR.…”
Section: Evidence Update Since Study Submissionmentioning
confidence: 99%